Evaluation of certain food additives and contaminants : thirty-fifth report of the Joint FAO/WHO Expert Committee on Food Additives, meeting held in Rome from 29 May to 7 June 1989 - World Health Organization; Food and Agriculture Organization (Geneva : World Health Organization, 1982)
Presents the conclusions of an expert committee commissioned to evaluate the safety of various food additives and contaminants, with a view to recommending acceptable daily intakes for humans. Specifications for the identity and purity of food additives are also presented. The first part of the report contains a general discussion of principles governing the toxicological evaluation of enzyme preparations, flavours, and compounds that have a laxative effect. The main part of the report summarizes evaluations of toxicological data on selected emulsifiers, enzymes, flavouring agents, food colours, thickening agents, and other additives. Contaminants covered include patulin and polychlorinated biphenyls.
Keywords: Evaluation of certain food